Transatlantic Relations under Stress: European and American Attitudes towards Intervention and Prevention - Fulvio Attina (Romanian Journal of European Affairs)
In this article, attention is called on the American attempt to change the international rules of intervention, and the impact this choice has on transatlantic relations. Hegemonic theory of world politics is the theoretical framework of the analysis. At the same time, the evolutionary world politics model is adopted to understand change in world politics. In the first section of the article, a set of concepts for the analysis of the structure of government of the world political system is presented. The second section is about the current phase of hegemonic politics and the state of transatlantic relations. The third section analyzes the issue of external military intervention to change domestic regimes and President Bush’s prevention doctrine. In the last section of the article, the attitudes and policies of the European Union and American governments on prevention are examined and confronted.